2005
DOI: 10.1038/sj.cdd.4401798
|View full text |Cite
|
Sign up to set email alerts
|

CaM-kinaseII-dependent commitment to microcystin-induced apoptosis is coupled to cell budding, but not to shrinkage or chromatin hypercondensation

Abstract: The protein phosphatase inhibitor microcystin-LR (MC) induced hepatocyte apoptosis mediated by the calciumcalmodulin-dependent multifunctional protein kinase II (CaM-KII). CaMKII antagonists were added at various times after MC to define for how long the cells depended on CaMKII activity to be committed to execute the various parameters of death. Shrinkage and nonpolarized budding were reversible and not coupled to commitment. A critical commitment step was observed 15-20 min after MC (0.5 lM) addition. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 40 publications
1
44
0
Order By: Relevance
“…Reports of liver cancer due to consumption of microcystins containing drinking water have increased substantially recently (Ouellette and Wilhelm 2003;Codd et al 2005). Krakstad et al (2006) reported that the PPinhibiting toxins induce morphological alteration compatible with apoptosis in different cell types. Ding et al (1999) found that MC-LR has strong mutagenicity and induced DNA damage in rat hepatocytes.…”
Section: Cyclic Peptides (Microcystins and Nodularins)mentioning
confidence: 99%
“…Reports of liver cancer due to consumption of microcystins containing drinking water have increased substantially recently (Ouellette and Wilhelm 2003;Codd et al 2005). Krakstad et al (2006) reported that the PPinhibiting toxins induce morphological alteration compatible with apoptosis in different cell types. Ding et al (1999) found that MC-LR has strong mutagenicity and induced DNA damage in rat hepatocytes.…”
Section: Cyclic Peptides (Microcystins and Nodularins)mentioning
confidence: 99%
“…However, in this study, BAPTA-AM inhibited the decrease of p-CaMKII induced by AlCl 3 , which proves that AlCl 3 increased the phosphorylated CaMKII by increasing [Ca 2+ ]i. In addition, overexpression of p-CaMKII is involved in apoptosis [43,44] and causes oxidative stress response [45]. Odagiri et al [46] found that the activated Ca 2+ / CaMKII signal pathway induce oxidative stress, which leads to myocyte apoptosis in rats.…”
Section: Fig 5 Amentioning
confidence: 47%
“…For examination of ultrastructure, HL60 cells were fixed and further processed as described previously. 22 …”
Section: Assessment Of Apoptosismentioning
confidence: 99%
“…The pellets were washed in 5% TCA, and then with water-saturated ether before being dissolved in 5 mmol/L Tris buffer, pH 8, containing 8.4 M urea, 2% 3-[(3-cholamidopropyl)dimethylammonio]propanesulfonate (CHAPS), and 100 mmol/L dithioerythritol. Aliquots were diluted in sodium dodecyl sulfate (SDS) loading buffer for SDS-polyacrylamide gel electrophoresis (PAGE) analysis, 22 or the incorporated radioactivity determined by liquid scintillation counting. 24 Isolation of RNA and its use as template for in vitro protein synthesis HL60 cells (10 7 cells) were pelleted, the pellet was lysed in 1 mL of TRIzol (Invitrogen), and RNA was isolated.…”
Section: Metabolic Labeling Of Cellsmentioning
confidence: 99%